Reduced-cost surrogate modelling of compact microwave components by two-level kriging interpolation. Issue 6 (2nd June 2020) - Koziel, Slawomir; Pietrenko-Dabrowska, Anna
ABSTRACT: Full-wave electromagnetic (EM) analysis is a versatile tool for evaluating the performance of high-frequency components. Its potential drawback is its high computational cost, inhibiting the execution of EM-driven tasks requiring massive simulations. The applicability of equivalent network models is limited owing to the topological complexity of compact microstrip components because of EM cross-coupling effects. Development of alternative representations (surrogate models) is therefore necessary. This article proposes a two-level methodology for reliable modelling of compact microstrip components. The keystone is to define the surrogate domain using the first-level model approximating the set of pre-existing reference designs. This limits the volume of the parameter space region that needs to be sampled when constructing the second-level model. The presented approach provides far greater accuracy than conventional methods and is capable of establishing surrogates covering wide ranges of geometric parameters and operating conditions of a particular structure. Applications for parametric optimization are also provided.